Komposisi dan Struktur Tumbuhan Bawah pada Habitat yang Diinvasi Tumbuhan Invasif di Kawasan Wisata Geopark Silokek Kabupaten Sijunjung - Solfiyeni, Solfiyeni; Sari, Anita Mayang; Chairul, Chairul; Mukhtar, Erizal (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The Silokek Geopark area, Sijunjung Regency, is one of the tourist areas in West Sumatra Province which has a high level of biodiversity, which can be disrupted due to the presence of invasive plants. A study has been carried out which aims to determine the composition and structure of undergrowth in habitats invaded by weeds in the Silokek Geopark tourist area, Sijunjung Regency. This research was conducted from September to December 2022 using the quadratic method and plotting by purposive sampling with a plot size of 10 x 10 m with a sub-plot measuring 2 x 2 m. The composition of undergrowth in the habitat invaded by weeds found 24 families, 38 genera, 38 species, and 1049 individuals. Among the undergrowth found, there were 12 families, 20 genera, 20 species and 532 individuals of invasive plants with the dominant family being Asteraceae (30.41%), and the co-dominant family being Nephrolepidaceae and Poaceae with a percentage of 17 each. .83% and 11.63%. The highest important value index was in Nephrolepis biserrata (28.42%) and the lowest was in Musa acuminata (0.76%). The most dominant weed species was Mikania michranta with an IVI of 18.79%. The diversity index of the understorey plants in this area is categorized as high with a diversity index (H’ = 3.24). Weed plant species are more successful in dominating open and disturbed areas with high levels of light intensity, gaps or wide gaps and forest edges can be utilized by invasive plant species to grow optimally.